Evaluation of the Portfolio of Regional Development Investment Projects - World Bank Group (World Bank, Washington, DC, 2016)
In the context of Romania’s push toward sustainable and inclusive development, the government has asked the World Bank to support the harmonization of public investments financed by the European Union and the state budget. The current report describes the national program for local development (PNDL’s) framework and project cycle and provides an overview of the program’s project portfolio in 2014. It also draws a number of preliminary observations and presents some potential policy measures, based on a review of 289 technical-economic documentations (in most cases feasibility studies) for new investments proposed for PNDL financing in 2014. The aim is to understand gaps and opportunities in the PNDL’s programming and implementation, and also to help develop the MRDPA’s capacity for assessing received proposals. This report seeks to contribute to the overall objective of improving the design and implementation of state-budget-funded investment programs under the Ministry of Regional Development and Public Administration (MRDPA) - primarily the PNDL. Chapter one gives introduction; chapter two presents PNDL background and portfolio assessment; chapter three presents main challenges related to the quality of projects submitted for PNDL financing; and chapter four presents preliminary observations and policy measures recommendations.